2020
DOI: 10.1186/s43055-020-00261-8
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT findings of COVID-19-infected patients, are there differences between pediatric and adult patients? A systematic review

Abstract: Background: Purpose of this study was to deliver a report of chest CT findings of COVID-19-infected pediatric and adult patients and to make an age-based comparison. A systematic search was conducted in accordance with PRIS MA guidelines to identify relevant studies in the electronic databases of PubMed, Scopus, ProQuest, ScienceDirect, and Web of Sciences from January 1, 2020 to March 27, 2020 using search terms in the titles and abstracts. Based on our inclusion and exclusion criteria, 762 articles were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The reverse halo sign (atoll sign) (i.e., areas of GGO with peripheral consolidation) is frequently observed [ 3 ]; in this study, the frequency of the reverse halo sign was 12%. Furthermore, the halo sign, which is a consolidative nodule or mass with peripheral GGO, was found in 11% of the patients in this study; it is uncommon in adults and could reach 50% in children [ 18 ]. The pleural transparent line or subpleural sparing is another CT sign found in 26.5%, whereas in previous studies, the reported frequency of subpleural sparing was 6–53.2% [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 98%
“…The reverse halo sign (atoll sign) (i.e., areas of GGO with peripheral consolidation) is frequently observed [ 3 ]; in this study, the frequency of the reverse halo sign was 12%. Furthermore, the halo sign, which is a consolidative nodule or mass with peripheral GGO, was found in 11% of the patients in this study; it is uncommon in adults and could reach 50% in children [ 18 ]. The pleural transparent line or subpleural sparing is another CT sign found in 26.5%, whereas in previous studies, the reported frequency of subpleural sparing was 6–53.2% [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 98%
“…We believe that PTS in COVID-19 is more common than expected because; (1) it may still be unfamiliar to radiologists as we saw it in previous published papers where it was not mentioned ( 2 , 3 ), (2) it may be mistaken for the atoll sign (difference is the central part; dense dot vs. central ground glass opacities) ( 4 , 5 ), (3) many pictorial derivatives such as double or incomplete outer dense rings may be seen ( 6 ), and (4) its possible confusion with organizing pneumonia which pathophysiologically makes this appearance possible in the early stages of the disease ( 7 , 8 ). At the early stage of COVID-19 when solitary lobule and its central bronchiole and artery become inflamed and fibrin and secretions began to fill the alveoli, PTS may be initially visible.…”
mentioning
confidence: 84%
“…The more pronounced difference between the groups corresponds to a higher frequency of unilateral lesions (30% of cases) and nodules (15%) in children ( 70 , 71 ); this implies that atypical presentations should be considered more often in pediatrics ( 67 ). Also, ~20% of the pediatric population have normal CT, which reinforces the importance of its performance in selected cases ( 70 ).…”
Section: Radiological Findingsmentioning
confidence: 99%
“…In comparison to adults, children have a generalized peripheral distribution of lesions ( 68 ) and a lower percentage of cases with GGOs, consolidation, crazy paving pattern, pleural effusion, and bilateral compromise ( 70 ). The more pronounced difference between the groups corresponds to a higher frequency of unilateral lesions (30% of cases) and nodules (15%) in children ( 70 , 71 ); this implies that atypical presentations should be considered more often in pediatrics ( 67 ). Also, ~20% of the pediatric population have normal CT, which reinforces the importance of its performance in selected cases ( 70 ).…”
Section: Radiological Findingsmentioning
confidence: 99%